2012
DOI: 10.1002/nau.22327
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence after surgery for pelvic organ prolapse

Abstract: Preoperative SUI or UUI is the most important predictor of SUI and UUI postoperatively. BMI and COPD were identified as important risk factors for SUI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 27 publications
9
64
0
4
Order By: Relevance
“…2 Persson et al and Lensen et al also observed that increased BMI was a positively associated risk factor for the development of OSUI. 22,23 The same was observed in our study.…”
Section: Discussionsupporting
confidence: 91%
“…2 Persson et al and Lensen et al also observed that increased BMI was a positively associated risk factor for the development of OSUI. 22,23 The same was observed in our study.…”
Section: Discussionsupporting
confidence: 91%
“…2 Based on incontinence status, we defined the following patient groups that closely relate to clinical practice: (1) women with symptomatic coexisting SUI; (2) women asymptomatic for SUI (with or without occult SUI); and (3) women asymptomatic for SUI with occult SUI. We pooled the outcomes for the different anti-incontinence procedures, because they are equally effective in the treatment of SUI.…”
Section: Data Extractionmentioning
confidence: 99%
“…Earlier reviews and studies suggested the same, but evidence for this is still limited. 2,[46][47][48] It remains a problem that there is no consensus in diagnosing occult SUI, and different methods to detect occult SUI were used in the studies included in our review.…”
Section: Interpretation In the Light Of Other Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…1 These women have increased risk to still experience SUI after prolapse repair. 2 When surgical correction of POP is indicated, there are two strategies to treat co-existing SUI: a one-step strategy (combined prolapse and incontinence surgery) or a two-step strategy (correct the prolapse first and evaluate incontinence afterwards). Evidence supporting the value of combination surgery is still limited in these women and two reviews recognised the need for further research.…”
Section: Introductionmentioning
confidence: 99%